2013
DOI: 10.1073/pnas.1309712110
|View full text |Cite
|
Sign up to set email alerts
|

Emphasis of spatial cues in the temporal fine structure during the rising segments of amplitude-modulated sounds

Abstract: The ability to locate the direction of a target sound in a background of competing sources is critical to the survival of many species and important for human communication. Nevertheless, brain mechanisms that provide for such accurate localization abilities remain poorly understood. In particular, it remains unclear how the auditory brain is able to extract reliable spatial information directly from the source when competing sounds and reflections dominate all but the earliest moments of the sound wave reachi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 24 publications
11
63
0
Order By: Relevance
“…That is, sound onsets may play a dominant role in ITD processing at both low and high frequencies, even when the onset of the envelope is itself diotic. A similar phenomenon has been reported in the lateralization of 500 Hz binaural beat stimuli subjected to periodic diotic amplitude modulation at a rate of 32 Hz (Dietz et al, 2013). In that study, listeners' perception of lateral position was strongly dominated by the finestructure ITD associated with the rising slope of the periodic modulation envelope.…”
Section: Fig 3 Upper Panelsupporting
confidence: 83%
See 2 more Smart Citations
“…That is, sound onsets may play a dominant role in ITD processing at both low and high frequencies, even when the onset of the envelope is itself diotic. A similar phenomenon has been reported in the lateralization of 500 Hz binaural beat stimuli subjected to periodic diotic amplitude modulation at a rate of 32 Hz (Dietz et al, 2013). In that study, listeners' perception of lateral position was strongly dominated by the finestructure ITD associated with the rising slope of the periodic modulation envelope.…”
Section: Fig 3 Upper Panelsupporting
confidence: 83%
“…The current results suggest similar temporal weighting of ITD for both such cases (unmodulated low-frequency tones and rapidly modulated high-frequency sounds). The "special" case, then, is that of slow modulations at high frequency, which appear capable of signaling ITD effectively with each modulation cycle, similarly to the case for slow modulations at low frequency (Dietz et al, 2013).…”
Section: The Role Of Instantaneous Itd Magnitudementioning
confidence: 99%
See 1 more Smart Citation
“…Another possibility is that, at early processing stages, sound intensity increments are not associated with changes in distance but are simply salient events. For instance, interaural spatial cues occurring at intensity increments are weighted strongly when computing left-right location (39,40). A strong effect of leftright congruence between increasing-intensity sounds and visual targets (41) further supports this reasoning.…”
Section: Perception Of Motion In Distance But Not Changes In Overall mentioning
confidence: 73%
“…The results showed a strong influence of attack and pause parameters, even outside of the physiological ITD range, which is relevant for ITD enhancement in binaural cochlear Chapter 5 General conclusions implant processors. In an imaging study, Dietz et al (2013a) found that the attack segment in an amplitude-modulated signal might be the region in which the auditory system is particularly sensitive to interaural timing differences, leading to reliable ITD "glimpes" even in reverberant conditions. In conclusion, the results from study 2 identify the most important localization-relevant parts of a periodically amplitude modulated signal.…”
Section: Chapter 5 General Conclusionmentioning
confidence: 99%